The Mechanism of Energy Coupling in H+/Na+-Pumping Membrane Pyrophosphatase-Possibilities and Probabilities - Baykov Alexander A; Anashkin Viktor A; Malinen Anssi M; Bogachev Alexander V (MDPI, 2022)
Membrane pyrophosphatases (mPPases) found in plant vacuoles and some prokaryotes and protists are ancient cation pumps that couple pyrophosphate hydrolysis with the H+ and/or Na+ transport out of the cytoplasm. Because this function is reversible, mPPases play a role in maintaining the level of cytoplasmic pyrophosphate, a known regulator of numerous metabolic reactions. mPPases arouse interest because they are among the simplest membrane transporters and have no homologs among known ion pumps. Detailed phylogenetic studies have revealed various subtypes of mPPases and suggested their roles in the evolution of the "sodium" and "proton" bioenergetics. This treatise focuses on the mechanistic aspects of the transport reaction, namely, the coupling step, the role of the chemically produced proton, subunit cooperation, and the relationship between the proton and sodium ion transport. The available data identify H+-PPases as the first non-oxidoreductase pump with a "direct-coupling" mechanism, i.e., the transported proton is produced in the coupled chemical reaction. They also support a "billiard" hypothesis, which unifies the H+ and Na+ transport mechanisms in mPPase and, probably, other transporters.